Glaucoma at a tertiary referral eye hospital in Nepal - Paudyal, I; Thapa, SS; Paudyal, G; Gurung, R; Ruit, S (Nepalese Journal of Ophthalmology, 2011)
Background: Glaucoma is an important cause of blindness. Objective: To report the distribution of various types of glaucoma among patients presenting to a tertiary eye hospital in Nepal. Materials and methods: All new patients visiting the hospital between March 2007 and February 2008 underwent a comprehensive eye examination. Whenever glaucoma was suspected, patients were referred to fellowship-trained glaucoma specialists. Patients received a comprehensive glaucoma workup including applanation tonometry, stereoscopic examination of the optic nerve head performed by the glaucoma specialists, and a Humphrey visual field analysis (SITA 24 - 2). Results: 447 patients were newly diagnosed with glaucoma. 171 (38.2 %) patients had primary open-angle glaucoma (POAG), while 143 (32 %) had primary angle-closure glaucoma (PACG). The average age of presentation of patients with POAG was 65.78 ± 9.1 years, while the average age for PACG patients was 54.6 ±12.8 years. 30 (21 %) patients with PACG had acute angle-closure on presentation, while 113 (79 %) had chronic angle closure glaucoma. 107 (75 %) of these patients with PACG had visual acuity of less than 3/60 (20/ 400) in the worse eye at presentation. The most common form of secondary glaucoma was lens-induced (5.3 %), followed by neovascular (3.2 %) and uveitic glaucoma (3.2 %). Conclusion: The most common glaucoma seen in a tertiary referral eye hospital of Nepal is primary open-angle glaucoma. Among the angle-closure glaucoma, chronic angle-closure is the most common. Lens-induced glaucoma is still the commonest cause of secondary glaucoma. Keywords: glaucoma, open-angle, angle-closure, lens-induced DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5263 Nepal J Ophthalmol 2011; 3(2): 123-127